ASSA: Agricultural Marketplace Application in the Distribution of Goods with GPS Tracking - Ulva, Ananda Faridhatul; Yulisda, Desvina; Fhonna, Rizky Putra; Qamal, Mukti; Fadhliani, Fadhliani (LPPI Yayasan Almahmudi bin Dahlan, 2024)
Agriculture in North Aceh District, with the number of Milleneal Farmers increasing every year, has become a major issue. The problem is that many farmers still lack access to markets, long and inefficient distribution chains and lack of transparency in the distribution delivery chain. So that with the ASSA application, the agricultural marketplace application with the GPS tracking feature can optimise the distribution channel by monitoring real-time movements of both product origin, delivery conditions and estimated time of arrival. In order for this research to succeed using the R&D (Research and Development) method, which is a systematic approach in creating new applications and making improvements. From the results of the implementation of the ASSA application in all villages in North Aceh District 90% experienced satisfaction in using the ASSA application, and 5% there are still users who experience bugs or errors, so this application will be improved next.